1982
DOI: 10.2337/diacare.5.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acarbose on the 24-Hour Blood Glucose Profile and Pattern of Carbohydrate Absorption

Abstract: Acarbose (Bay g 5421) is a powerful alpha-glucoside hydrolase inhibitor of potential value in the treatment of diabetes and hypoglycemic dumping syndrome after gastric surgery. The extent of its use may be limited by symptoms produced by carbohydrate malabsorption. To minimize these, the action of low doses of acarbose on 24-h blood glucose profiles and hydrogen evolution have been studied on four ambulant volunteers on control diets, after exclusion of sucrose and also after addition of guar in an attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…Assuming that the mean 2-h post-load glucose level in patients with IGT, when treated with placebo, increases 0.25 mmol/L in 3 years, that the mean level in patients treated with acarbose decreases 0.25 mmol/L in 3 years [21,22], and that the standard deviation of the levels is stable in both groups and remains equal to the standard deviation in the comparable subpopulation of the Hoorn Study survey (0.67 mmol/L) [3], we determined that we would need 47 participants in each treatment group to demonstrate the resulting 0.5-mmol/L difference as statistically significant with alpha (two-sided) = 0.05 and beta = 0.05. Thus, we needed complete data from 94 participants to provide sufficient statistical power.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that the mean 2-h post-load glucose level in patients with IGT, when treated with placebo, increases 0.25 mmol/L in 3 years, that the mean level in patients treated with acarbose decreases 0.25 mmol/L in 3 years [21,22], and that the standard deviation of the levels is stable in both groups and remains equal to the standard deviation in the comparable subpopulation of the Hoorn Study survey (0.67 mmol/L) [3], we determined that we would need 47 participants in each treatment group to demonstrate the resulting 0.5-mmol/L difference as statistically significant with alpha (two-sided) = 0.05 and beta = 0.05. Thus, we needed complete data from 94 participants to provide sufficient statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this dose because previous studies had demonstrated that it significantly lowered postprandial blood glucose with fewer side effects than a dose of 300 mg/day [20][21][22]. Participants were instructed to take their tablets with the first bite of a meal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al [26] have shown that substi tuting starch for sucrose may reduce carbo hydrate malabsorption with small doses of acarbose. The same group found that 50 mg of miglitol almost blunted the glycemic re sponse after 50 g potato starch over 4 h with only slight increases in breath hydrogen ex halation and symptoms [21], Moreover, dia betic patients on adequate diets reported only slight symptoms of carbohydrate mal absorption after 50 or 100 mg of miglitol [27].…”
Section: Discussionmentioning
confidence: 99%
“…This digestion process is important for glucose absorption from the intestine to the blood, and in principle, control of HPA activity can be used as a means of controlling blood glucose levels. In fact, HPA activity has been correlated to post-prandial blood glucose levels (17)(18)(19), and inhibitors of ␣-amylase have been successfully used in the treatment of diseases such as diabetes or obesity where control of the blood glucose level is essential (20).…”
mentioning
confidence: 99%